IOT And AI Integration in Healthcare: Advancing Operational Efficiency and Patient Monitoring - Mohammad Yasin; Sunil Kanojiya; Mahbub Hasan; Mahzabin Binte Rahman; Saif Ahmad (International Journal of Medical Science and Public Health Research, 2025)
The fast digitalization of the healthcare sector has increased the rate at which the Internet of Things (IoT) and Artificial Intelligence (AI) can be combined as two complementary technologies that can change the way patients are monitored and operational efficiencies are improved. Smart sensors on wearables and smart medical devices process tremendous amounts of real time health and operational data due to IoT-enabled devices. Combined with AI algorithms, these streams of data can be converted into actionable information that can be used to facilitate predictive diagnostics, proactive measures, and the prioritization of available resources. The paper explores the possibility of utilizing the union of IoT and AI to strengthen healthcare systems by improving patient outcomes and at the same time, tackling the urgent issues of cost, scalability and efficiency. The paper approaches the subject of conducting a mixed-method investigation using a combination of the empirical findings of recent deployments and a systematic review of the available literature to discuss the technological structure, clinical implementation, and the cost-benefit of IoT-AI integration. Findings indicate that health institutions that implement such solutions record decreases in hospital readmission, reduced waiting time by patients, better management of chronic diseases and great cost savings in operations. Moreover, AIs can be used to enhance IoT monitoring systems to provide sustained and customized care outside the clinical environment, which promotes patient-centeredness and health outcomes. Even with the promising advances, there are still challenges on interoperability, security of data and ethical issues with regard to patient privacy. The originality of this work is in its comprehensive assessment of the IoT and AI as a single system as opposed to two distinct technologies with a systematic approach to adopting scalable, safe, and patient-focused online health solutions by hospitals and policymakers.